The development of semi-auto flood door barrier - Supar, Khairi; Sheikh Ismail, Sheikh Mohamad Naqib; Azmi, Muhammad Azammudin; Jafri, Ariff Izzudin; Mohammad Azmi, Mohamad Azim; Ahmad, Hilton (2024)
Flood barriers play a crucial role in mitigating the devastating impact of flooding events. This project focuses on testing flood barriers to enhance their effectiveness and reliability in reducing the adverse effects of floods. The recent floods in Malaysia have resulted in significant infrastructure destruction, underscoring the urgent need for flood mitigation strategies to minimize fatalities and property damage. Flood control techniques aim to confine water and prevent it from inundating buildings, particularly those situated in flood-prone areas. To ensure the optimal performance of new flood barriers, multiple standardized tests must be conducted during their development. This study specifically investigates the feasibility and effectiveness of temporary flood barriers (TFBs) in reducing the severe consequences of floods. By exploring the potential of TFBs and assessing their suitability as a flood mitigation strategy, this research aims to contribute to the development of effective flood control measures. TFBs are physical structures erected at the entrances of buildings to safeguard their infrastructure from water damage during flood events. They serve to minimize property damage and are particularly beneficial in flood-prone areas. The study encompasses a comprehensive discussion of successful TFB applications, along with an overview of the various types of TFBs available on the market, including their associated advantages and limitations. By examining and evaluating TFBs, this research seeks to provide valuable insights that can inform the development of effective flood control measures in Malaysia